Mechanical engineering design - Shigley, Joseph Edward; Mischke, Charles R. (McGraw Hill, 2001)
Covering almost all the important machine elements encountered in the machine design course, this book emphasizes on developing good design and problem-solving skills. It also offers an opportunity to bring computer tools into the course. It includes examples from industry and real engineering situations, along with a selection of case studies.